DIFFERENTIAL DESIGNING FOR FSAE MOTOR SPORTS VEHICLE JCU - Pieta MARCIANO; Greg WHEATLEY; Ahmed ALI (Scientific Journal of Silesian University of Technology. Series Transport)
The objective of this work was to design a differential assembly for an FSAE motor sports vehicle. The designed differential system consists of 3 braces made of AISI 1045 steel. The output shafts were made of AISI 4140 steel with hardened splines. These shafts were initially going to drive 94 mm constant velocity shafts. A 75 mm tripod joint was used to minimize the weight and cost of the system. The housing was held together with grade 12.8 hex head bolts, and the shafts were bolted onto the tri-pod joints using bolts of grade 8.8 which complies with FSAE rules. The input shaft which acts on the differential itself is made of EN36A steel and is where the drive sprocket is bolted to. All components were modeled using Finite Element Analysis to determine stresses and displacements under operating conditions.